2020
DOI: 10.3389/fpsyg.2020.573961
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Dreams: Network Analysis of Dream Content During the COVID-19 Lockdown

Abstract: We used crowdsourcing (CS) to examine how COVID-19 lockdown affects the content of dreams and nightmares. The CS took place on the sixth week of the lockdown. Over the course of 1 week, 4,275 respondents (mean age 43, SD = 14 years) assessed their sleep, and 811 reported their dream content. Overall, respondents slept substantially more (54.2%) but reported an average increase of awakenings (28.6%) and nightmares (26%) from the pre-pandemic situation. We transcribed the content of the dreams into word lists an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
136
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(150 citation statements)
references
References 42 publications
11
136
3
Order By: Relevance
“…The observed enhancement of negative emotions in dreams, with a predominance of fear, is consistent with the few existing data pointing to a spread of negative emotions [ 61 ], anxiety-related [MacKay and DeCicco, 2020] and pandemic-related content [ 48 ] in dreams during the 2020 lockdown. Moreover, we found a higher proportion of dream negative emotions in females, younger subjects, and participants with lower sleep quality, disruptive nocturnal behaviours, depressive and state/trait anxiety symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…The observed enhancement of negative emotions in dreams, with a predominance of fear, is consistent with the few existing data pointing to a spread of negative emotions [ 61 ], anxiety-related [MacKay and DeCicco, 2020] and pandemic-related content [ 48 ] in dreams during the 2020 lockdown. Moreover, we found a higher proportion of dream negative emotions in females, younger subjects, and participants with lower sleep quality, disruptive nocturnal behaviours, depressive and state/trait anxiety symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…Schredl and Bulkeley ( 2020 ) reported greater dream recall and a higher likelihood of negative dream content during the pandemic. Pesonen et al ( 2020 ) found that 55% of reported dreams classified as “distressing” were pandemic-specific and included themes such as social distancing, personal protective equipment (PPE), and the infectivity of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies analyzing dreams during the COVID-19 pandemic have largely used data from general populations with diverse demographic characteristics (Altena et al, 2020 ; Pesonen et al, 2020 ; Schredl and Bulkeley, 2020 ). Studies within a population with more demographic homogeneity may highlight the shared experience of pandemic lockdown, as similarities of lifestyle, age, and finances may result in further commonalities within dream content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data from web-based surveys reported a high prevalence of poor sleep quality in the general population during the COVID-19 outbreak (Cellini et al, 2020;Huang & Zhao, 2020;Xue et al, 2020). Moreover, recent studies have observed several pandemic-specific dream contents in the general population, such as failures in social distancing or coronavirus contagion, showing an association with increased stress (Pesonen et al, 2020). The presence of distressing dreams related with specific traumatic experiences, as a prolonged treatment in the Intensive Care Unit due to COVID-19, is relevant because it may represent an early symptom of the onset of stress-related disorders, being considered a diagnostic criterion for Posttraumatic Stress Disorder (PTSD) in the 5th ed.…”
Section: Introductionmentioning
confidence: 99%